2022
DOI: 10.7759/cureus.33071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Face-Mask Use on Dry Eye Disease Evaluated Using Self-Reported Ocular Surface Disease Index Scores: A Cross-Sectional Study on Nurses in Saudi Arabia

Abstract: Background: Wearing face masks has been an essential part of healthcare workers’ lives since the coronavirus disease 2019 (COVID-19) pandemic. This study aims to determine the association between prolonged face mask-wearing and dry eye disorder (DED) among female nurses. Methods: An online questionnaire-based cross-sectional study was conducted at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, between May 2021 and February 2022. It covered sociodemographic data, conditions associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a recent study, Motwani et al ( 27 ) found that wearing a face mask for more than three to six hours per day could exacerbate or increase the symptoms of DED among healthcare professionals who had previously had the condition and were under the age of 40. According to research by Alsulami et al ( 31 ) among female nursing staff, wearing a mask for more than six hours per day was substantially related to moderate to severe DED. In addition, Shalaby et al ( 25 ) study discovered a substantial positive link between the OSDI, corneal staining, and the amount of hours per day spent wearing a face mask, as well as a strong negative correlation with the Schirmer test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Motwani et al ( 27 ) found that wearing a face mask for more than three to six hours per day could exacerbate or increase the symptoms of DED among healthcare professionals who had previously had the condition and were under the age of 40. According to research by Alsulami et al ( 31 ) among female nursing staff, wearing a mask for more than six hours per day was substantially related to moderate to severe DED. In addition, Shalaby et al ( 25 ) study discovered a substantial positive link between the OSDI, corneal staining, and the amount of hours per day spent wearing a face mask, as well as a strong negative correlation with the Schirmer test.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Shalaby et al ( 25 ) study discovered a substantial positive link between the OSDI, corneal staining, and the amount of hours per day spent wearing a face mask, as well as a strong negative correlation with the Schirmer test. According to Alsulami et al ( 31 ) among female nursing personnel, wearing a face mask for more than six hours per day was substantially related with moderate to severe DED. Boccardo documented that in the general population, retailers were a possible risk factor for MADE; they reported more MADE compared to the other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest causes of discomfort are also breathing problems [42,[50][51][52][53], especially in people suffering from asthma [53]. The prolonged face mask use can also affect ocular health by exacerbating dry eye symptoms [54,55,56], [57] or creating visual artifacts due to improper fit [58], which, as one of the existing cases showed, also plays a role in worsening those symptoms by directing the exhaled air into the user's eyes [59]. Worth noting is that one of the studies discussed in this paper regarding the influence of mask use on TMJ disorders, also showed that the improper fit of a face mask can impair this joint's health due to repetitive movements [35], which could be induced by discomfort coming from blowing exhaled air into the eyes.…”
Section: Discussionmentioning
confidence: 99%